STUDI KOMPARASI KADAR FLAVONOID TOTAL PADA BUNGA ROSELLA MERAH (Hibiscus sabdariffa L.) ASAL KABUPATEN LUWU UTARA PROVINSI SULAWESI SELATAN DAN KABUPATEN KEDIRI PROVINSI JAWA TIMUR - Saida I. Suradji; Ahmad Najib; Aktsar Roskiana Ahmad (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Red Roselle (Hibiscus sabdariffa L.) is a medicinal plant used by the public as drugs. This plant is efficacious because one contains chemical constituents are flavonoids. Comparative Study of total Flavonoid content in red Roselle (Hibiscus sabdariffa L.) from North Luwu district of South Sulawesi province and the province of East Java Kediri district has done. The aim of study to determine of total flavonoid content in Kediri regency and district of North Luwu using a spectrophotometer. Extraction is done by maceration method using 96% ethanol. Phytochemical screening using the color reaction identification and determine content of Colorimetric method using UV-Vis spectrophotometry at the maximum wavelength of 417 nm. Meanwhile the yield extract red Rosellafrom Kediri (sample I) 12.703% and red Rosella from north Luwu (sample II) 10.44%. Test phytochemical to sample I and sample II positive containing Flavonoids. Test total Flavonoid content to sample I is 0.02816% and sample II is 0.2075%.